2023
DOI: 10.1101/2023.10.12.561972
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Restriction of Arginine Induces Antibiotic Tolerance inStaphylococcus aureus

Jeffrey A. Freiberg,
Valeria M. Reyes Ruiz,
Erin R. Green
et al.

Abstract: Staphylococcus aureusis responsible for a substantial number of invasive infections globally each year. These infections are problematic because they are frequently recalcitrant to antibiotic treatment, particularly when they are caused by Methicillin-ResistantStaphylococcus aureus(MRSA). Antibiotic tolerance, the ability for bacteria to persist despite normally lethal doses of antibiotics, is responsible for most antibiotic treatment failure in MRSA infections. To understand how antibiotic tolerance is induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 64 publications
0
1
0
Order By: Relevance
“…Indeed, previous studies have shown the importance of arginine in the survival of S. aureus during infection as it utilizes it as a source of carbon and nitrogen, it also has been shown to have a pertinent role in biofilm formation as well as pH homestasis ( Lindgren et al, 2014 ). Morever, recent report by Freiberg et al have shown induction of antibiotic tolerance by S. aureus communities due to depletion of argninie ( Freiberg et al, 2023 ). However, to the best of our knoweldge no direct report on the role of arginine in the antimicrobial resistance mechanism has been reported.…”
Section: Disscussionmentioning
confidence: 99%
“…Indeed, previous studies have shown the importance of arginine in the survival of S. aureus during infection as it utilizes it as a source of carbon and nitrogen, it also has been shown to have a pertinent role in biofilm formation as well as pH homestasis ( Lindgren et al, 2014 ). Morever, recent report by Freiberg et al have shown induction of antibiotic tolerance by S. aureus communities due to depletion of argninie ( Freiberg et al, 2023 ). However, to the best of our knoweldge no direct report on the role of arginine in the antimicrobial resistance mechanism has been reported.…”
Section: Disscussionmentioning
confidence: 99%